Musik Kesenian Tradisional Parrawana pada Era Modernisasi di Polewali Mandar - Syaribulan Syaribulan (Universitas Muhammadiyah Makassar, 2017)
The existence of traditional art music parrawana in the era of modernization. This research uses qualitative descriptive approach supported by femonology approach through purposive sampling technique. Data collection is used by observation, interview, and documentation. The categories of informants used were key informants, key informants, and additional informants. Technique validity technique triangulation data, triangulation time and triangulation of data source. The results can be concluded that the existence of art Parrawana in the era of modernization according to the tradition of the ancestors and not affected by the flow of modernization is always demanding development. Although Polewali Mandar people have known modernization in their changing lives and mindset have been following the times, but they still maintain the preservation of traditional art as inherited by the ancestors in the era of modernization. Efforts made by the community, community and government is to invite young people to preserve the arts Parrawana.Keywords: Music, Parrawana, Modernization